International Accounting Standards Harmonisation: The Case of Iran Privatisation - Roudaki, Jamal (The International Journal of Accounting and Business Society, 2005)
Accounting standards harmonisation literature shows that from the beginning of the twenty first century IASs and IFRSs are receiving increasing attention from professional accounting bodies and stock market authorities of developed and developing countries more than ever before. Consequently number of countries chose to join the IAS users have increased dramatically in recent years. The objective of this paper is to explore how Iranian Accounting Standards Board achieves harmonisation with IASs and IFRSs while government using some efforts to develop local stock market as means of privatisation. Tehran Stock Exchange which is involved in the third wave of country privatisation required companies to prepare their financial reports using National Accounting Standards. These standards are in harmony with IASs and IFRs as they are developed based on the same procedure of IASBâ€™s â€œdue processâ€. In the same way, proposed projects of Iran Accounting Standards Boards aim to develop conceptual framework in order to establish a platform for standard setting. Due to recent development in privatisation in relation to internationally harmonised national accounting and auditing standards the standard setting in Iran is in the state of flex national and international wise. Key words: International Standards Harmonisation, International Accounting Standards, Privatisation and accounting standards, Iran Accounting Standards